Small Molecule Drug Discovery for Neglected Tropical Snakebite. (May 2021) - Clare, Rachel H.; Hall, Steven R.; Patel, Rohit N.; Casewell, Nicholas R.
Abstract : Snakebite envenoming is responsible for as many as 138 000 deaths annually, making it the world's most lethal neglected tropical disease (NTD). There is an urgent need to improve snakebite treatment, which currently relies on outdated and poorly tolerated biologic antivenoms that are often weakly efficacious, must be given intravenously in a healthcare setting, and are expensive to those who need them the most. Herein we describe the challenges associated with the discovery and development of new snakebite treatments and detail the great potential of venom toxin-inhibiting small molecule drugs. We finish by highlighting successful enabling strategies applied to other NTDs that could be exploited to facilitate the development of next-generation small molecule–based snakebite treatments. Highlights: Snakebite is a life-threatening neglected tropical disease that causes >100 000 deaths each year, and there are many deficiencies associated with current biologic antivenom therapies. Certain small molecule toxin-inhibiting drugs have demonstrated highly promising preclinical efficacy against snakebite, and the potential to administer such drugs orally in snakebite-affected communities offers an exciting new treatment strategy. The chemical space explored to date for snakebite drugs is highly limited. Drug discovery programs are urgently needed to broaden the snakebite drug portfolio and to overcome the challenges associated with developing single-drug or combination drug therapies. The diverse enabling strategies successfully used by drug discovery programmes for other neglected tropical diseases provide promising avenues for delivering future snakebite therapeutics.